2021
DOI: 10.1172/jci152088
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning–driven identification of early-life air toxic combinations associated with childhood asthma outcomes

Abstract: Air pollution is a well-known contributor to asthma. Air toxics are hazardous air pollutants that cause or may cause serious health effects. While individual air toxics have been associated with asthma, only a limited number of studies have specifically examined combinations of air toxics associated with the disease. We geocoded air toxic levels from the US National Air Toxics Assessment (NATA) to residential locations for participants of our AiRway in Asthma (ARIA) study. We then applied Data-driven ExposurE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Another study 84 assessed multi exposure models across the life course and interactions with epithelial barriers and the microbiome, which are exemplified by the exposome concept that can be explained as the measure of all exposures of an individual related to health and disease. Two more ongoing studies 85,86 are investigating artificial intelligence applications and computational science in allergy.…”
Section: Clinical Implications and Future Research Directionsmentioning
confidence: 99%
“…Another study 84 assessed multi exposure models across the life course and interactions with epithelial barriers and the microbiome, which are exemplified by the exposome concept that can be explained as the measure of all exposures of an individual related to health and disease. Two more ongoing studies 85,86 are investigating artificial intelligence applications and computational science in allergy.…”
Section: Clinical Implications and Future Research Directionsmentioning
confidence: 99%
“…Furthermore, it was found that exposure to particulate matter, sulfur dioxide, and nitrogen oxides are a risk factor for developing lung cancer (Manisalidis et al, 2020). Moreover, exposure to benzene vapor from vehicles emission causes a wide range of health problems such as hematologic disorders and lung diseases (Li et al, 2021)…”
Section: 30% N O a T Y P I A M I L D A T Y P I A M O D E R A T E A T ...mentioning
confidence: 99%
“…Moreover, a predictive ML model might not be the optimal model for inference . However, in recent epidemiological studies, interpretable tree-based ML tools were used to discover simultaneously co-occurring chemicals, similar to classical Weighted Quantile Sum (WQS) Regression models. Separately in computational biology, using a novel ML algorithm called random intersection trees, Basu et al , introduced the “signed iterative random forest” (SiRF) algorithm to discover interactions through collective activities. SiRF can efficiently search for the few stable and highly occurring interactions instead of going through each possible interaction term.…”
Section: Introductionmentioning
confidence: 99%